Short Assessment of the Big Five: Robust Across Survey Methods Except Telephone Interviewing - Frieder R. Lang; Dennis John; Oliver Lüdtke; Jürgen Schupp; Gert G. Wagner (Behavior Research Methods, 2011)
We examined measurement invariance and age-related robustness of a short 15-item Big Five Inventory (BFI–S) of personality dimensions, which is well suited for applications in large-scale multidisciplinary surveys. The BFI–S was assessed in three different interviewing conditions: computer-assisted or paper-assisted face-to-face interviewing, computer-assisted telephone interviewing, and a self-administered questionnaire. Randomized probability samples from a large-scale German panel survey and a related probability telephone study were used in order to test method effects on self-report measures of personality characteristics across early, middle, and late adulthood. Exploratory structural equation modeling was used in order to test for measurement invariance of the five-factor model of personality trait domains across different assessment methods. For the short inventory, findings suggest strong robustness of self-report measures of personality dimensions among young and middle-aged adults. In old age, telephone interviewing was associated with greater distortions in reliable personality assessment. It is concluded that the greater mental workload of telephone interviewing limits the reliability of self-report personality assessment. Face-to-face surveys and self-administrated questionnaire completion are clearly better suited than phone surveys when personality traits in age-heterogeneous samples are assessed.
Additional information: This article is published with open access at Springerlink.com: doi:10.3758/s13428-011-0066-z
Keywords: 300; Big Five; Personality; Survey method; Face-to-face; Telephone interview; Self-administrated questionnaire; Exploratory structural equation modeling (ESEM)